Who Owns the Kurils? The Question of Territorial Sovereignty Arising from the Kuril Islands Dispute - Geach, Jonathan (South African Yearbook of International Law, 2021)
The Kuril Islands are a group of volcanic islands that stretch between Hokkaido in Japan and Kamchatka in Russia. They are the subject of an ongoing territorial dispute between Russia and Japan, which is largely rooted in historical developments which took place during the closing chapters of the Second World War. There are several legal questions which arise from the dispute between Russia and Japan pertaining to the establishment of territorial sovereignty. These questions are whether a term within the Yalta Conference Agreement lawfully gave a right to the USSR to the sovereign territory of Japan, in the absence of Japanese consent. Whether the USSR had violated international law by annexing the Kuril Islands. Whether Japan still had a lawful claim to the Kuril Islands after the conclusion of the Treaty of San-Francisco, and whether the islands claimed by Japan do indeed form part of the Kuril Islands. This article analyses each of these questions in order to determine whether sovereignty has in fact been lawfully established by Russia over the Kuril Islands and whether Japanese territorial claims have any merit in international law.